Identification of the Vitamin D Receptor in Osteoblasts and Chondrocytes But Not Osteoclasts in Mouse Bone. (March 2014) - Wang, Yongji; Zhu, Jinge; DeLuca, Hector F
ABSTRACT Bone is clearly a target of vitamin D and as expected, the vitamin D receptor (VDR) is expressed in osteoblasts. However, the presence of VDR in other cells such as osteocytes, osteoclasts, chondroclasts, and chondrocytes is uncertain. Because of difficulties in obtaining sections of undecalcified adult bone, identification of the site of VDR expression in adult bone tissue has been problematic. In addition, the antibodies to VDR used in previous studies lacked specificity, a property crucial for unambiguous conclusions. In the present study, VDR in the various cells from neonatal and adult mouse bone tissues was identified by a highly specific and sensitive immunohistochemistry method following bone decalcification with EGTA. For accurate evaluation of weak immunosignals, samples from Demay VDR knockout mice were used as negative control. Molecular markers were used to identify cell types. Our results showed that EGTA‐decalcification of bone tissue had no detectable effect on the immunoreactivity of VDR. VDR was found in osteoblasts and hypertrophic chondrocytes but not in the multinucleated osteoclasts, chondroclasts, and bone marrow stromal cells. Of interest is the finding that immature osteoblasts contain large amounts of VDR, whereas the levels are low or undetectable in mature osteoblasts including bone lining cells and osteocytes. Proliferating chondrocytes appear devoid of VDR, although low levels were found in the hypertrophic chondrocytes. These data demonstrate that osteoblasts and chondrocytes are major targets of 1α, 25‐dihydroxyvitamin D, but osteoclasts and chondroclasts are minor targets or not at all. A high level of VDR was found in the immature osteoblasts located in the cancellous bone, indicating that they are major targets of 1α, 25‐dihydroxyvitamin D. Thus, the immature osteoblasts are perhaps responsible for the vitamin D hormone signaling resulting in calcium mobilization and in osteogenesis. © 2014 American Society for Bone and Mineral Research.